Monitoring training load and identifying fatigue in young elite speed skaters using machine learning methods - Bolten, M. (University of Twente, 2024)
Monitoring training load is crucial for enhancing sports performance, as excessive load can lead to fatigue accumulation and decreased performance. Research has extensively investigated sports monitoring techniques, including measuring external and internal loads. Understanding fatigue states helps coaches prevent nonfunctional overreaching and optimize training for improved per formance. Continuous monitoring, such as using non-invasive maximal effort tests, is essential to detect declines in performance and adjust training accordingly.